Role and Function of Regulatory T Cell in Chronic Rhinosinusitis with Nasal Polyposis - Chenyang Lei; Juan Jiang; Yanyan Zhang; Gaoyun Xiong (Journal of Immunology Research, 2022)
Chronic rhinosinusitis with nasal polyps (CRSwNP) is a subtype of chronic rhinosinusitis characterized by high edema in the stroma, albumin deposition, and formation of pseudocysts. The pathogenesis of CRSwNP is not yet fully understood. Regulatory T (Treg) cells are a subset of CD4+ T cells that play a suppressive immunoregulatory role in the process of CRSwNP. Recent studies have found that there was a significant reduction in Treg cells in polyp tissues, which leads to the onset of CRSwNP. An imbalance between Th17 and Treg cells can also aggravate inflammation toward the Th2 type. This review focuses on our understanding of the function and role of Treg cells and their regulatory factors and clinical significance in CRSwNP. We also summarize the current drug treatments for CRSwNP with Tregs as the potential therapeutic target, which will provide new ideas for the treatment of CRSwNP in the future.